Effect of specific non-pharmaceutical intervention policies on SARS-CoV-2 transmission in the counties of the United States - Bingyi Yang (Nature Portfolio, 2021)
Disentangling the impacts of non-pharmaceutical interventions on COVID-19 transmission is challenging as they have been used in different combinations across time and space. This study shows that, early in the epidemic, school/daycare closures and stopping nursing home visits were associated with the biggest reduction in transmission in the United States.